2006
DOI: 10.1196/annals.1364.014
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Stress Reactivity After Long‐Term Treatment with Paroxetine in Women with Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is typically accompanied by both acute and chronic alterations in the stress response. These alterations have mostly been described in individuals under baseline conditions, but studies have also used a challenge model to assess the role of the hypothalamic-pituitary-adrenal (HPA) axis in the stress response. The purpose of this article was to assess the effect of long-term treatment with the selective reuptake inhibitor (SSRI), paroxetine, on stress reactivity in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 80 publications
(139 reference statements)
2
34
0
1
Order By: Relevance
“…High levels of corticosterone, corticotropin-releasing hormone, stress or exposure to a new environment have been shown to impair the induction of long term potentiation (Kim and Diamond, 2002;Xu et al, 1998), proliferation and survival of neurons and dendritic spines in the hippocampus (Chen et al, 2008;Pham et al, 2003). Treatment with different SSRIs has been repeatedly found to reduce cortisol levels in patients with anxiety disorders (Lenze et al, 2011;Vermetten et al, 2006), as well as corticosterone levels in animal studies (Buhl et al, 2010;Schmidt et al, 2007). In light of these findings, it is assumed that a normalization of the HPA axis might be part of the mechanism by which SSRIs create their anxiolytic therapeutic effects.…”
Section: Discussionmentioning
confidence: 98%
“…High levels of corticosterone, corticotropin-releasing hormone, stress or exposure to a new environment have been shown to impair the induction of long term potentiation (Kim and Diamond, 2002;Xu et al, 1998), proliferation and survival of neurons and dendritic spines in the hippocampus (Chen et al, 2008;Pham et al, 2003). Treatment with different SSRIs has been repeatedly found to reduce cortisol levels in patients with anxiety disorders (Lenze et al, 2011;Vermetten et al, 2006), as well as corticosterone levels in animal studies (Buhl et al, 2010;Schmidt et al, 2007). In light of these findings, it is assumed that a normalization of the HPA axis might be part of the mechanism by which SSRIs create their anxiolytic therapeutic effects.…”
Section: Discussionmentioning
confidence: 98%
“…In an open-label study we showed a 5% increase in hippocampal volume after 9 months of treatment with paroxetine, as well as a 30% improvement in verbal declarative memory function measured with neuropsychological testing . Paroxetine treatment was also associated with a decreased cortisol and heart rate response to a stressful task (Vermetten et al, 2006b). …”
Section: Effects Of Treatment On the Brain In Ptsdmentioning
confidence: 99%
“…These findings indicate that phenytoin has an effect on symptoms as well as brain structure in PTSD patients. In a second study, patients with PTSD were shown to have an increase in hippocampal volume and memory function with paroxetine [96], and a decrease in cortisol responsiveness to a stressful cognitive challenge [160]. One case report showed decreased inferior frontal, prefrontal, and insula blood flow measured with PET in response to war-related sounds.…”
Section: Effects Of Pharmacotherapy On Brain Function and Structure Imentioning
confidence: 99%